Novel Therapeutic Approaches of Pulmonary Arterial Hypertension - Tyagi, Sanjay; Batra, Vishal (International Journal of Angiology, 2019)
Pulmonary arterial hypertension (PAH) is an uncommon disease characterized progressive remodeling of pulmonary vasculature. Although treatment for PAH have improved in last two decades but the outcome remains fatal. Currently, the therapies for PAH target three well-established pathways the nitric oxide (NO) pathway, endothelin receptors, and prostanoids. There are multiple potential targets for development of newer drugs in PAH which requires meticulous research and clinical trials.
Keywords: pulmonary arterial hypertension; therapeutic; novel; phosphodiesterase; nitric oxide; prostaglandins; endothelin receptor